Upaya Penguatan Karakter tidak Suka Berbohong Melalui Metode Bercerita "Pinokio Si Boneka kayu" Pada Anak Usia Dini - Mastuti, Wening Dwi; Sabardilla, Atiqa (Jurnal Empowerment, 2025)
The objective of this research is to examine the process of enhancing character development in young children using the storytelling approach. This study employed a descriptive qualitative methodology. The study was conducted at the PGRI Tegalsari Kindergarten, involving children between the ages of 4 and 5, as well as teachers. The data gathering methods employed in this research encompassed observation, interviews, and documentation. The findings of this study indicate that the moral virtue derived from the narrative "Pinocchio the Wooden Puppet" is the ethical imperative of refraining from falsehoods towards others. The challenges encountered by instructors in cultivating the character of pupils include the presence of apathetic parents who show insufficient concern for their children, both in the educational setting and in assigning homework, as well as the absence of sufficient educational resources.